Climatic determinants of changes in the ice regime of Carpathian rivers - Fukś, Maksymilian; Wiejaczka, Łukasz (Quaestiones Geographicae, 2025)
The study addresses the influence of climatic conditions on changes in the ice regime of Carpathian rivers (Central Europe) over the period 1980–2020. The main objective of this study is to identify interrelationships between air temperature, water temperature, river flow, and changes in the occurrence of ice cover (IC) in mountain areas. Rivers that are not significantly influenced by human activity (i.e. seminatural) were selected for analysis. Analyses were based on data obtained from 13 hydrological stations, 7 climatological stations, and the Climatic Research Unit gridded Time Series (CRU-TS) high-resolution climatological dataset. The study showed a decrease in the frequency of IC in the study area, reaching 7.25 days per decade, with the greatest changes recorded in November and February. At the beginning of the winter period (November), the decrease in the frequency of IC is mainly influenced by the increasing water temperature (by an average of 0.85°C per decade), whereas in the middle of the winter period (especially February), it is influenced by the increase in discharge of the studied rivers (by 1.1 m3 per decade on average in February). Both the increase in water temperature and the increase in discharge during the winter period are due to the increase in air temperature, averaging 0.47°C per decade during the winter period.